2021
DOI: 10.3389/fneur.2021.696244
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Treatment Is Associated to Increased Internal Carotid Artery Calcification

Abstract: Background: Long-term treatment with the vitamin K antagonist warfarin is widely used for the prevention of venous thrombosis and thromboembolism. However, vitamin K antagonists may promote arterial calcification, a phenomenon that has been previously studied in coronary and peripheral arteries, but not in extracranial carotid arteries. In this observational cohort study, we investigated whether warfarin treatment is associated with calcification of atherosclerotic carotid arteries.Methods: Overall, 500 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Warfarin increases calcium deposition in the thoracic and abdominal aortas of uremic rats, which can be ameliorated by high doses of vitamin K2 ( 40 ) ( Table 2 ). Consistent with in vivo studies, clinical studies have shown that warfarin significantly increases the occurrence and progression of VC ( 92 , 93 ). Although a post hoc analysis of the ViKCoVaC (effect of Vitamin-K1 and Colchicine on Vascular Calcification activity in subjects with Diabetes Mellitus) double-blind randomized controlled trial showed that vitamin K1 supplements (10 mg/day) delay the progression of CAC in diabetic patients ( 94 ), clinical evidence for VC delay in CKD patients is scarce.…”
Section: Findings and Discussionsupporting
confidence: 62%
“…Warfarin increases calcium deposition in the thoracic and abdominal aortas of uremic rats, which can be ameliorated by high doses of vitamin K2 ( 40 ) ( Table 2 ). Consistent with in vivo studies, clinical studies have shown that warfarin significantly increases the occurrence and progression of VC ( 92 , 93 ). Although a post hoc analysis of the ViKCoVaC (effect of Vitamin-K1 and Colchicine on Vascular Calcification activity in subjects with Diabetes Mellitus) double-blind randomized controlled trial showed that vitamin K1 supplements (10 mg/day) delay the progression of CAC in diabetic patients ( 94 ), clinical evidence for VC delay in CKD patients is scarce.…”
Section: Findings and Discussionsupporting
confidence: 62%
“…Nine study cohorts were cross-sectional with an unspecified duration of treatment (28,33,43,44,46,47,53,56,58). The medical history of the patients included coronary artery disease (CAD) (27,32,39), chronic kidney disease CKD (including patients with ESRD) (29, 40-43, 46, 47, 53, 55), calcific aortic valve disease or aortic stenosis (CAVD/AS) (28,56,57,60), atrial fibrillation (AF/NVAF) (28,29,32,34,38,39,49,54,55,58,61), metallic prosthetic valves (36), lower limb amputation (44), carotid atherectomy (48), non-traumatic cerebral hemorrhage (50) or underwent cardiac CT (33, 35) or mammography (40, 52) tests for diagnostic or screening purposes. Two studies included the general population from health registries (30,59).…”
Section: Search Results and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Several studies have shown that anticoagulant therapy warfarin is associated with increased calcification in various districts, including coronary arteries [89], carotids [90], lower-extremity arteries [91], abdominal aorta, and heart valves [92]. Warfarin is a competitor of vitamin K, and there is evidence that it accelerates calcification by affecting vitamin K-dependent MGP activation, hence, reducing the physiological anti-calcific properties of this protein [93].…”
Section: Warfarinmentioning
confidence: 99%